The Analysis of Instructional Media as Cirebonese Cultural Representative Related to Students’ Learning Styles in Peer Teaching Activity - Jaufillaili, Jaufillaili; Linda, Linda (Universitas Swadaya Gunung Jati, 2016)
In this research, the writers observed the peer-teaching activity in Teaching and Listening for Children class. The writers intended to find out: 1) What is the dominant students‟ learning styles in the class? 2) What are the most dominant instructional media as Cirebonese cultural representative used by the students in peer-teaching activity in the class? 3) How are the instructional media used by the students in peer-teaching activity related to their learning styles? The theory of learning style used in this research was from Pritchard (2009) that was strengthened by Fauziati (2010). This was a qualitative research. The research instruments were Batch‟s Learning style inventory test and observation sheet. The result showed that: 1) The dominant students‟ learning styles in the class was visual learning styles. From forty (41) one students, twenty one (21) students were visual learners. 2) The most dominant instructional media as Cirebonese cultural representative used by the students in peer-teaching activity in the class was picture. Pictures as instructional media were used by almost all groups with different learning styles preferences. 3) The instructional media used by the students in peer-teaching activity related to their learning styles could be concluded as follows: auditory learners uses a sound record, visual learners used pictures, kinesthetic/tactile learners used paper that should be folded by the students (involving physical activity), and multi-learning style learners used video that involved audio-visual activity for their students.